TEMPAT PENGEMBANGAN GRIT - Hans Jonathan; Alvin Hadiwono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
One of the problems in human life is individualism. This is because humans spend too much time at work and at home, so they rarely do social activities, along with the existence of social media that causes people to socialize with each other. This particular problem will be discussed in "Open Architecture as Third Place" project, which discusses how to create a third place as a place for people to socialize with each other and also as a public information space. The issue raised in this project is about "Grit" where people can learn how to grow grits within themselves to achieve the goals they want to achieve in the future. The project location is on Jalan Tanjung Duren Utara. This site is quite strategic for this third place project because it is close to First Place and Second Place where this project can become a permeability. This third place project is wished for people to be able to grow grits in themselves so that they can achieve their goals in their lives and can achieve their life goals that they have set. The method used in research is Field Survey, Literature Study, and Precedent Study. The results obtained are the design of the building as a "Grit Improvement Space". The main program in this project is the Experimental Room, Workshop, and Exhibition along with the supporting programs namely Co-Working Space, Library, and Late Night Street Food. Keywords: grit; human; permeability; social  AbstrakPermasalahan dalam kehidupan manusia salah satunya individualisme. Hal ini disebabkan karena manusia terlalu banyak menghabiskan waktunya di tempat kerja dan di rumah, maka orang akan jarang sekali melakukan kegiatan sosial. Dengan adanya media sosial juga menyebabkan manusia bersosialisasi satu sama lain. Permasalahan utama yang akan dibahas di proyek ini adalah "Open Architecture sebagai Third Place" yang membahas bagaimana cara menciptakan tempat ketiga sebagai tempat untuk manusia saling bersosialisasi satu sama lain dan juga sebagai tempat publik informasi. Isu yang diangkat dalam proyek ini adalah mengenai "Grit" dimana orang dapat belajar cara menumbuhkan grit di dalam dirinya untuk mencapai goals yang mereka ingin capai di masa depan. Lokasi proyek berada di Jalan Tanjung Duren Utara. Tapak ini cukup strategis untuk proyek third place ini karena berdekatan dengan First Place dan Second Place sehingga proyek ini dapat menjadi rembesan (permeabilitas). Di proyek third place ini diharapkan orang bisa menumbuhkan grit dalam dirinya sehingga mereka bisa mencapai targetnya dalam hidup mereka dan dapat mencapai tujuan hidupnya yang telah mereka tentukan.  Metode yang digunakan dalam penelitian adalah Survey Lapangan, Studi Literatur, dan Studi Preseden. Hasil penelitian yang didapatkan adalah perancangan bangunan sebagai "Tempat Pengembangan Grit". Program utama dalam proyek ini adalah Experimental Room, Workshop, dan Pameran. Lalu juga ada program pendukung yaitu Co - Working Space, Library, dan Late Night Street Food.